Gestión de proyectos productivos y su influencia en la iniciativa emprendedora de los estudiantes de secundaria de la Institución Educativa N° 80183, El Pallar Alto - Huamachuco, provincia de Sánchez Carrión, año 2017 - Barrios Pacheco, Abigail (2018)
The general objective of this research is to determine the extent to which the management of productive projects influences the entrepreneurial initiative of participating students of Educational Institution N°80183 - Pallar Alto, Huamachuco District, province of Sanchez Carrion, 2017. The problem raised was: To what extent does the Management of Productive Projects influence the Entrepreneurship of the participating students of Educational Institution N°80183 - El Pallar Alto, District of Huamachuco, Province of Sanchez Carrion, year 2017?. The research design used was no experimental, cross-correlational / causal. For data collection, a population made up of the first and second grade students of the educational institution under study was used, to whom a survey was applied, whose instrument was the questionnaire. After obtaining the results and being analyzed, the hypothesis was proved: The management of productive projects has a high influence on the Entrepreneurship Initiative of the students of the Educational Institution N°80183 - El Pallar Alto, District of Huamachuco, Province of Sanchez Carrion, year 2017. The main conclusion is to develop a good management of productive projects towards the students, that is to say, teach the processes of implementation of a business idea, influencing their entrepreneurial initiative awakening in them their abilities and business skills. Therefore it is recommended that the development of productive projects implies that the teachers in charge must be professionally prepared to be able to guide the student in the realization of their ideas, which in turn will help them to strengthen their self-esteem, as well as the development of their skills and abilities.